OPTIMASI BAURAN PEMASARAN PELAYANAN KESEHATAN DALAM MENINGKATKAN KEPUASAN PASIEN: STUDI KASUS DI RSUD DR. IR. IWAN BOKINGS KABUPATEN BOALEMO - Usu, Idrus; R. Karundeng, Deby; Hendra, Hendra (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This study aims to optimize the healthcare service marketing mix to enhance patient satisfaction at RSUD Dr. Ir. Iwan Bokings, Boalemo Regency. This case study explores the impact of marketing mix elements on patient satisfaction. The research uses a quantitative method with a survey approach. The sample consists of 100 respondents selected using accidental sampling. Data was collected through a questionnaire representing eight marketing mix variables (product, price, place, promotion, people, process, physical evidence) and patient satisfaction. Data analysis was performed using multiple linear regression. The results show that product, price, promotion, place, and people have a positive and significant impact on patient satisfaction, while process and physical evidence do not have a significant effect. The significant positive influence of product is related to the effectiveness of diagnosis, treatment success, and the patient's experience during care. Transparent and fair pricing, as well as effective promotion through social media and word of mouth, increase patient satisfaction. The hospital's strategic location and cleanliness of the environment also contribute to patient satisfaction. Although interactions with medical and non-medical staff have a positive influence, the impact is not significant. Process and physical evidence, although important, are not substantial enough to significantly influence patient satisfaction.